Effect of grape pomace supplement on growth performance, gastrointestinal microbiota, and methane production in Tan lambs - Cheng, Xindong; Du, Xia; Liang, Yanping; Degen, Abraham Allan; Wu, Xiukun; Ji, Kaixi; Gao, Qiaoxian; Xin, Guosheng; Cong, Haitao; Yang, Guo (Frontiers in Microbiology, 2023)
Grape pomace (GP), a by-product in wine production, is nutritious and can be used as a feed ingredient for ruminants; however, its role in shaping sheep gastrointestinal tract (GIT) microbiota is unclear. We conducted a controlled trial using a randomized block design with 10 Tan lambs fed a control diet (CD) and 10 Tan lambs fed a pelleted diet containing 8% GP (dry matter basis) for 46 days. Rumen, jejunum, cecum, and colon bacterial and archaeal composition were identified by 16S rRNA gene sequencing. Dry matter intake (DMI) was greater (P < 0.05) in the GP than CD group. However, there was no difference in average daily gain (ADG, P < 0.05) and feed conversion ratio (FCR, P < 0.05) between the two groups. The GP group had a greater abundance of Prevotella 1 and Prevotella 7 in the rumen; of Sharpe, Ruminococcaceae 2, and [Ruminococcus] gauvreauii group in the jejunum; of Ruminococcaceae UCG-014 and Romboutsia in the cecum, and Prevotella UCG-001 in the colon; but lesser Rikenellaceae RC9 gut group in the rumen and cecum, and Ruminococcaceae UCG-005 and Ruminococcaceae UCG-010 in the colon than the CD group. The pathways of carbohydrate metabolism, such as L-rhamnose degradation in the rumen, starch and glycogen degradation in the jejunum, galactose degradation in the cecum, and mixed acid fermentation and mannan degradation in the colon were up-graded; whereas, the pathways of tricarboxylic acid (TCA) cycle VIII, and pyruvate fermentation to acetone in the rumen and colon were down-graded with GP. The archaeal incomplete reductive TCA cycle was enriched in the rumen, jejunum, and colon; whereas, the methanogenesis from H2 and CO2, the cofactors of methanogenesis, including coenzyme M, coenzyme B, and factor 420 biosynthesis were decreased in the colon. The study concluded that a diet including GP at 8% DM did not affect ADG or FCR in Tan lambs. However, there were some potential benefits, such as enhancing propionate production by microbiota and pathways in the GIT, promoting B-vitamin production in the rumen, facilitating starch degradation and amino acid biosynthesis in the jejunum, and reducing methanogenesis in the colon.